PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN PADA RUMAH MAKAN DI KABUPATEN NGAWI - Wulan Jayanti; Supri Wahyudi Utomo; Juli Murwani (Assets: Jurnal Akuntansi dan Pendidikan, 2013)
This study aims to examine the influence of service quality on customer satisfaction in the restaurant of Ngawi resident. Population in this research is customer of Ngawi resident restaurant. The number of samples considered representative and reflect the characteristics of the population were 50 respondents. The hypothesis tested in this study with the Product Moment Correlation Analysis Method and t test. The results of this study indicate there is a positive and significant effect of service quality on customer satisfaction in Ngawi resident restaurant.